Characteristics of Environmental influences on Child Health Outcomes (ECHO) Cohorts Recruited During Pregnancy. Issue 4 (July 2021) - Faro, Elissa Z.; Sauder, Katherine A.; Anderson, Amber L.; Dunlop, Anne L.; Kerver, Jean M.; McGrath, Monica; Roary, Mary; Roman, Carolyn W.; Weidinger, Cara; Huddleston, Kathi C.
Abstract: Purpose: The objective of this study was to characterize the study designs, recruitment strategies, and other study characteristics among cohorts that initiated during pregnancy as part of the Environmental influences on Child Health Outcomes (ECHO) program. Methods: ECHO research programs (cohorts) were reviewed. Only those who had or were currently recruiting during pregnancy were surveyed in 2018 about research recruitment strategies (participant incentives, study burden, community collaboration, and cultural adaptations). Data are presented with cohort characteristics (location, inclusion and exclusion criteria, sociodemographics, medical information, behavioral factors, and biospecimens). Results: Forty-seven of the 84 ECHO pediatric cohorts recruited during pregnancy. Findings demonstrate various recruitment strategies, domains of data collection, and biospecimen collection are all characteristics of successful cohorts. Clinical Implications: These data that include over 50, 000 children from families across the country, many in underserved areas, will be used for research with the potential to lead to profound policy changes. Prenatal conditions such as maternal age, obesity, depression, and drug use can be examined using study data, including biological markers, from pregnancy through childbirth and into childhood and will inform national policies on the role of early life exposures and underlying mechanisms of disease progression. Abstract : In this study, characteristics of cohorts that were initiated during pregnancy as part of the Environmental influences on Child Health Outcomes program are detailed. The cohorts include over 50, 000 children from families across the country, many in underserved areas. Data will be used for research with the potential to inform national policies on the role of early life exposures and underlying mechanisms of disease progression.